Aphidius ervi Teratocytes Release Enolase and Fatty Acid Binding Protein Through Exosomal Vesicles - Salvia, Rosanna; Grimaldi, Annalisa; Girardello, Rossana; Scieuzo, Carmen; Scala, Andrea; Bufo, Sabino A.; Vogel, Heiko; Falabella, Patrizia (Frontiers in Physiology, 2019)
The molecular bases of the host-parasitoid interactions in the biological system Acyrthosiphon pisum (Harris) (Homoptera, Aphididae) - Aphidius ervi (Haliday) (Hymenoptera, Braconidae) have been elucidated allowing the identification of a gamma-glutamyl transpeptidase, the active component of maternal venom secretion, and teratocytes, the embryonic parasitic factors responsible for the host physiology regulation after parasitization. Teratocytes, cells deriving from the dissociation of serosa, the parasitoid embryonic membrane, are responsible for extra-oral digestion of host tissues in order to provide a suitable nutritional environment for the development of parasitoid larvae. Teratocytes rapidly grow in size without undergoing any cell division, synthesize, and release in the host hemolymph two proteins: a Fatty Acid Binding Protein (Ae-FABP) and an Enolase (Ae-ENO). Ae-FABP is involved in transport of fatty acids deriving from host tissues to the parasitoid larva. Ae-ENO is an extracellular glycolytic enzyme that functions as a plasminogen like receptor inducing its activation to plasmin. Both Ae-FABP and Ae-ENO lack their signal peptides and are released in the extracellular environment through an unknown secretion pathway. Here we investigated the unconventional mechanism by which teratocytes release Ae-FABP and Ae-ENO in the extracellular space. Our results, obtained using Immunogold staining coupled with TEM and western blot analyses, show that these two proteins are localized in vesicles released by teratocytes. The specific dimension of these vesicles and the immunodetection of ALIX and HSP70, two exosome markers, strongly supports the hypothesis that vesicles are exosomes.